2007
DOI: 10.1074/jbc.m703777200
|View full text |Cite
|
Sign up to set email alerts
|

Replisome Fate upon Encountering a Leading Strand Block and Clearance from DNA by Recombination Proteins

Abstract: Replication forks that collapse upon encountering a leading strand lesion are reactivated by a recombinative repair process called replication restart. Using rolling circle DNA substrates to model replication forks, we examine the fate of the helicase and both DNA polymerases when the leading strand polymerase is blocked. We find that the helicase continues over 0.5 kb but less than 3 kb and that the lagging strand DNA polymerase remains active despite its connection to a stalled leading strand enzyme. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 67 publications
4
51
1
Order By: Relevance
“…25-27 and references therein), shorter RecA-filaments are formed in absence of RecFOR and are proposed to bind lagging-strand ssDNA produced during fork advance (24). Extension of RecA filaments toward the replisome destabilizes the Pol III*-replisome, facilitating its dissociation, consistent with our earlier in vitro observations that RecA dislodges Pol III* from a primed site (23). Another possibility is that RecA inhibits a component of Pol III*, either Pol III core, the clamp loader, or the τ subunit of the clamp loader.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…25-27 and references therein), shorter RecA-filaments are formed in absence of RecFOR and are proposed to bind lagging-strand ssDNA produced during fork advance (24). Extension of RecA filaments toward the replisome destabilizes the Pol III*-replisome, facilitating its dissociation, consistent with our earlier in vitro observations that RecA dislodges Pol III* from a primed site (23). Another possibility is that RecA inhibits a component of Pol III*, either Pol III core, the clamp loader, or the τ subunit of the clamp loader.…”
Section: Resultssupporting
confidence: 77%
“…Thus, RecA up-regulation during the SOS response should inhibit fork progression by Pol III*-β. Our earlier studies on the effect of RecA on Pol III*-β have also demonstrated that RecA can disassemble the replicase from DNA (23). Furthermore, a recent in vivo study using single-molecule techniques finds that RecA indeed binds to DNA at the replication fork, and favors disassembly of the Pol III replisome (24).…”
Section: Resultsmentioning
confidence: 99%
“…Pol III HE stalled by deprivation of two nucleotides is quite stable as it cycles between digestion of the nascent DNA and polymerization (48), and digestion of a DNA strand with a 3Ј-terminal dideoxymononucleotide by the 3Ј 3 5Ј exonuclease of the Pol III HE is slowed only by a factor of 6 compared with digestion of a DNA strand terminated with a 3Ј-deoxymononucleotide (49); thus, the cycle of polymerization/exonuclease digestion is unlikely to be perturbed significantly. Indeed, in experiments using a rolling circle DNA template, McInerney and O'Donnell (50) found that leading-strand synthesis could resume after blockages to the leading-strand polymerase (ddNTP addition) and the helicase (ATP depletion) were eliminated by diluting the reaction mixture. Furthermore, it was clear that DnaB was still present on these templates under these conditions because if we terminated DNA synthesis by the addition of the ddNTPs and then followed any subsequent reaction, products appeared representing the fully unwound, partially replicated leading-and lagging-strand sister duplexes (41) (Fig.…”
Section: An Assay For Replication Fork Reversal Using Bona Fide Replimentioning
confidence: 99%
“…Therefore, the described above properties of D. radiodurans proteins are likely to be conserved for E. coli homologs. While DNA binding and ATPase assays did not reveal specificity of RecF towards DNA junction, functional studies clearly evidence the role of RecF at ss/dsDNA junction (Chow and Courcelle, 2004;Handa et al, 2009;McInerney and O'Donnell, 2007;Morimatsu and Kowalczykowski, 2003;Webb et al, 1997). The potential specificity of RecF to ds/ssDNA junction is likely to require additional protein partners of recombination initiation reaction including SSB, RecO and RecA.…”
Section: The Lack Of Ss/dsdna Junction Specificitymentioning
confidence: 99%